2019
DOI: 10.3989/scimar.04862.22b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of <em>Homarus gammarus</em> (Crustacea: Decapoda: Nephropidae) catches and potential in a Mediterranean small-scale fishery

Abstract: The aim of this study was to obtain a better understanding of the exploitation pattern of the European lobster population in a fully representative small-scale fishery of the Mediterranean (Corsica, France) and to collect initial biological information on this species. Data were collected by scientific observers on board net fishing vessels for eight consecutive years from 2006 until 2013. Average annual catches were estimated at 6.7 t. Length frequencies indicated that exploitation focused on large individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 38 publications
2
19
0
1
Order By: Relevance
“…They also showed that anthropogenic impacts did not significantly affect H. gammarus genetic diversity. Exploitation patterns and biological data of H. gammarus around Corsica were reported by Pere et al [14]. In the absence of published data, parameters for complete population assessment of any crustacean species (i.e., sex, growth, age, and mortality), morphometric relationships, and allometry are useful tools to reveal population characteristics during growth [33,34], to estimate population biomass, to compare morphological traits between different species or populations across the distribution range [35][36][37], and to estimate functional maturity [27,38].…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…They also showed that anthropogenic impacts did not significantly affect H. gammarus genetic diversity. Exploitation patterns and biological data of H. gammarus around Corsica were reported by Pere et al [14]. In the absence of published data, parameters for complete population assessment of any crustacean species (i.e., sex, growth, age, and mortality), morphometric relationships, and allometry are useful tools to reveal population characteristics during growth [33,34], to estimate population biomass, to compare morphological traits between different species or populations across the distribution range [35][36][37], and to estimate functional maturity [27,38].…”
Section: Introductionmentioning
confidence: 76%
“…Around 80% of landings came from the North-Eastern Atlantic, while landings in Mediterranean countries never reached those levels [13]. New estimations confirmed the general underestimates of the FAO data in the French Mediterranean [14], suggesting that they might be generally accurate for the whole distribution. It was clearly demonstrated that specific lobster stocks in the Mediterranean suffered from overexploitation [15][16][17], with sharp declines in landings reported for more than a century [18,19].…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Namely, majority of marine stocks are considered fully exploited or overexploited ( Vasilakopoulos et al, 2014 ; Osio et al, 2015 ; Tsikliras et al, 2015 ; FAO, 2018 ). Nowadays, European lobster stocks are considered depleted due to significant declines in catches in many Mediterranean regions ( Lloret and Riera, 2008 ; Lotze et al, 2011 ; Pere et al, 2019 ), although stock assessment has not been performed yet. To support genetically informed European lobster fisheries management in the Adriatic Sea, 14 neutral microsatellites loci and partial mtDNA region were used to explore fine-scale genetic structure of species and migration patterns that affect genetic connectivity, by comparing 331 individuals sampled from the central and eastern regions of the Mediterranean.…”
Section: Discussionmentioning
confidence: 99%